2016
DOI: 10.3389/fvets.2016.00099
|View full text |Cite|
|
Sign up to set email alerts
|

Unfractionated and Low-Molecular-Weight Heparin and the Phosphodiesterase Inhibitors, IBMX and Cilostazol, Block Ex Vivo Equid Herpesvirus Type-1-Induced Platelet Activation

Abstract: Equid herpes virus type-1 (EHV-1) is a major pathogen of horses, causing abortion storms and outbreaks of herpes virus myeloencephalopathy. These clinical syndromes are partly attributed to ischemic injury from thrombosis in placental and spinal vessels. The mechanism of thrombosis in affected horses is unknown. We have previously shown that EHV-1 activates platelets through virus-associated tissue factor-initiated thrombin generation. Activated platelets participate in thrombus formation by providing a surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
(71 reference statements)
1
7
1
Order By: Relevance
“…In addition to within-horse variability in baseline platelet reactivity to EHV-1, we noted that the percentage of platelets expressing P selectin after exposure to low or high concentrations of the Ab4 strain were lower than what we have published previously ( 30 ). There are several possible explanations for this, including the use of different horses (with intrinsic variation in coagulation factor or inhibitor concentrations), the use of different lots of purified virus, or an effect of the change in protocol with decreased sample dilution.…”
Section: Resultscontrasting
confidence: 68%
See 2 more Smart Citations
“…In addition to within-horse variability in baseline platelet reactivity to EHV-1, we noted that the percentage of platelets expressing P selectin after exposure to low or high concentrations of the Ab4 strain were lower than what we have published previously ( 30 ). There are several possible explanations for this, including the use of different horses (with intrinsic variation in coagulation factor or inhibitor concentrations), the use of different lots of purified virus, or an effect of the change in protocol with decreased sample dilution.…”
Section: Resultscontrasting
confidence: 68%
“…The reaction was quenched with 0.6 ml of platelet buffer containing 0.2 mM supplemental GPRP and 2.5 mM calcium chloride and the samples were immediately analyzed with a flow cytometer (BD FACSCalibur, BD Biosciences, San Jose, CA, USA). For analysis, platelets were gated on their forward and side scatter characteristics and the percentage of P selectin-positive platelets determined from histogram plots, as we have previously described ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that, EHV-1 activates platelets through virus-associated tissue factor-initiated thrombin generation that participate in thrombus formation by providing a surface to localize coagulation factor complexes. Accordingly, using of anticoagulants that suppress thrombin generation or platelet inhibitors that impede post-receptor thrombin signaling (phosphodiesterase antagonists) would inhibit EHV-1-induced platelet activation (Stokol et al, 2016). Interestingly, subcutaneous injection of 25000 IU heparin to horses during EHV-1 outbreak resulted in lower EHM incidence (3.2%) than untreated horses (23.3%) (Walter et al, 2016).…”
Section: Treatmentmentioning
confidence: 99%
“… 25 , 50 , 53 Increased numbers of activated platelets and/or PLAs measured by flow cytometry have been described in horses after near-maximal treadmill exercise, 72 after induced infection with equine infectious anemia virus, 49 in the course of carbohydrate-induced laminitis, 71 and in vitro after incubation with lipopolysaccharides 9 and equid herpesvirus 1 ( Equid alphaherpesvirus 1 ). 60 62 Activation markers in horses with equine asthma after antigen challenge were expressed inconsistently, with increased activation in one study 29 and no difference to the control groups in 2 other studies. 20 , 30 In experimentally induced equine endotoxemia, platelet activation was not increased at the time of leukocyte nadir.…”
mentioning
confidence: 99%